2018
DOI: 10.1097/phh.0000000000000719
|View full text |Cite
|
Sign up to set email alerts
|

State Health Agencies' Perceptions of the Benefits of Accreditation

Abstract: The national voluntary accreditation program serves to encourage health agencies to seek departmental accreditation as a mechanism for continuous quality improvement. This study utilizes data from the 2016 Association of State and Territorial Health Officials Profile Survey to examine the perceived benefits of accreditation among state health agencies. Respondents answered questions on topics such as agency structure, workforce, and quality improvement activities. Frequencies and cross tabulations were conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Ultimately, national public health accreditation is purported to strengthen the delivery of public health services and programs, improve understanding of and responsiveness to community needs and assets, increase consistency in practice, support more efficient and effective use of resources, and improve overall population health outcomes. 9 Although the impact of this accreditation is still unfolding, state and local (civilian) health departments report several specific benefits that they’ve experienced already as a result of achieving accreditation including: Enable identification of department strengths and weaknesses 4 to address gapsDocument capacity to deliver core public health functions 4 Improve cross-organizational (i.e., within organization) collaboration 10 Promote transparency and accountability within and outside of the department 3 Stimulate quality and performance improvement 4,10,11 Improve communication 4 Strengthen the department’s culture of quality improve-ment 4,10,11 …”
Section: Conclusion and Considerationsmentioning
confidence: 99%
“…Ultimately, national public health accreditation is purported to strengthen the delivery of public health services and programs, improve understanding of and responsiveness to community needs and assets, increase consistency in practice, support more efficient and effective use of resources, and improve overall population health outcomes. 9 Although the impact of this accreditation is still unfolding, state and local (civilian) health departments report several specific benefits that they’ve experienced already as a result of achieving accreditation including: Enable identification of department strengths and weaknesses 4 to address gapsDocument capacity to deliver core public health functions 4 Improve cross-organizational (i.e., within organization) collaboration 10 Promote transparency and accountability within and outside of the department 3 Stimulate quality and performance improvement 4,10,11 Improve communication 4 Strengthen the department’s culture of quality improve-ment 4,10,11 …”
Section: Conclusion and Considerationsmentioning
confidence: 99%
“…8,12 Benefits that may be associated with accreditation in the area of workforce development include increased staff training and knowledge specific to QI 9 ; greater staff awareness of public health topics, including QI, evidence-based public health practice, and multisectoral collaboration 13 ; and increased efforts to identify and address training and workforce development deficiencies. 14 Another study of a limited number of health departments pursuing accreditation found that none of the agencies had plans for workforce development, QI, or performance management before initiating accreditation activities. 15 In addition to these outcomes, anticipated improvements in financial resources and expanded funding opportunities have been cited as motivators for pursuing and anticipated benefits of accreditation.…”
mentioning
confidence: 99%
“…15 In addition to these outcomes, anticipated improvements in financial resources and expanded funding opportunities have been cited as motivators for pursuing and anticipated benefits of accreditation. 14,16,17 Overall, few studies have assessed how accreditation has affected the financial status of health departments, including new or increased funding. Preliminary accreditation outcomes data indicate that approximately half of accredited health departments, at the time they were accredited for 1 year, reported that accreditation improved their health departments' competitiveness for funding 4,8 and utilization of resources.…”
mentioning
confidence: 99%
“…More recent studies have attempted to ascertain the value of national voluntary accreditation 10–18. For the most part, these studies relied on self-reported perspectives of individuals closely involved in the accreditation process 1214. They typically reported that it adds value and provides a benefit to their HDs.…”
mentioning
confidence: 99%
“…They typically reported that it adds value and provides a benefit to their HDs. However, the majority of these studies have been limited to LHDs13–17 and/or are limited by social desirability bias 1214,18. New contributions, such as the recent study by Ye and colleagues,15 address some concerns about social desirability bias by assessing what accreditation means to the workforce as a whole, rather than just to those closely involved.…”
mentioning
confidence: 99%